(untitled) - Kremenova, Iveta; Kovacikova, Martina (Doprava a spoje, 2010)
Paper deals with the questions behind the identification of key-factors of User-oriented web application development. The methods of its identification, source of information and also the content of each category are mentioned. The categories are Search, Display, Home Page and Navigation. These categories are decomposed to the table form. Paper also deals with the web application testing on the background of identified key factors. Testing was realized by the Department of Communications.